2022
DOI: 10.1186/s12943-022-01539-3
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LINC00680 functions as a ceRNA to promote esophageal squamous cell carcinoma progression through the miR-423-5p/PAK6 axis

Abstract: Background Esophageal squamous cell carcinoma (ESCC) is a common invasive malignancy worldwide with poor clinical outcomes. Increasing amount of long non-coding RNAs (lncRNAs) have been reported to be involved in cancer development. However, lncRNAs that are functional in ESCC and the underlying molecular mechanisms remain largely unknown. Methods Transcriptomic analysis was performed to identify dysregulated lncRNAs in ESCC tissue samples. The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 94 publications
0
51
0
Order By: Relevance
“…MiRNA expression is also regulated by DNA methylation ( 49 ). In recent years, many studies have found that long noncoding RNAs (lncRNAs) have the role of sponge, they can competitively adsorb miRNA, thereby inhibiting the regulation of miRNA on target genes ( 50 , 51 ). In future research, we will explore the causes and mechanisms of miR-375 expression changes in tumors from an epigenetic perspective and explore the feasibility of miRNA-375 as an anti-tumor drug.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA expression is also regulated by DNA methylation ( 49 ). In recent years, many studies have found that long noncoding RNAs (lncRNAs) have the role of sponge, they can competitively adsorb miRNA, thereby inhibiting the regulation of miRNA on target genes ( 50 , 51 ). In future research, we will explore the causes and mechanisms of miR-375 expression changes in tumors from an epigenetic perspective and explore the feasibility of miRNA-375 as an anti-tumor drug.…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein C2 (APOC2) is a lipoprotein lipase activator involved in fatty acid metabolism [ 45 ]. Most differentially expressed lncRNAs, such as AL121906.2 [ 46 ], AC092910.3 [ 47 ], AC005332.4 [ 48 ], and CASC9 [ 49 ], were upregulated in EAC subtype 1 and had been previously reported as prognostic biomarkers in multiple tumors. These findings highlighted the intrinsic molecular differences between the two EAC subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the common types of genetic medicines, microRNAs (miRNAs) are a group of non-coding small RNAs with a length of about 22 bp that silence target genes at the post-transcriptional level [7]. Current research confirms that miRNAs are involved in many physiological processes and pathological pathways, including embryonic development, tumorigenesis, and cardiac disease [8][9][10]. Studies have confirmed that in the brain tissue or serum of AD patients, many miRNAs have been identified as down-regulated and thought to be involved in the formation of senile plaques and neurofibrillary tangles [11].…”
Section: Introductionmentioning
confidence: 99%